Molecular Cloning And Characterisation Of 5'-Untranslated And Promoter Regions Of Peroxisome Proliferator Activated Receptor Alpha (PPARa) From Human[QP552.T68 C548 2003 f rb]. - PPSKJ, Pusat Pengajian Sains Kajihayat (2003)
Peroxisome proliferator-activated receptor alpha (PPARα) is a ligand-activated transcription factor which belongs to the nuclear receptor superfamily and regulates gene transcription by heterodimerizing with retinoic X receptor (RXR).